2022
DOI: 10.1039/d2bm00435f
|View full text |Cite
|
Sign up to set email alerts
|

A core–shell liquid metal-Cu nanoparticle with glutathione consumptionviaanin situreplacement strategy for tumor combination treatment of chemodynamic, microwave dynamic and microwave thermal therapy

Abstract: A stable core–shell spherical “storage pool” was obtained, which could realize the combination of chemodynamic, microwave dynamic and microwave thermal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Reproduced with permission. [144] Copyright 2022, Royal Society of Chemistry. (g) Schematic diagram of microwave sensitizer for MDT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [144] Copyright 2022, Royal Society of Chemistry. (g) Schematic diagram of microwave sensitizer for MDT.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al utilized liquid metal eutectic gallium indium to generate ROS under microwave irradiation to achieve a combination therapy with CDT (Figure 6e,f). [144] Wu et al synthesized eutectic gallium indium alloy to generate •OH and •O 2 − under microwave irradiation to achieve a combination of dynamic and thermal therapy (Figure 6g). [145] The generation mechanism of 6h-j).…”
Section: Driven By Microwavementioning
confidence: 99%
See 1 more Smart Citation
“…[ 83–85 ] In many cases, such shells exhibit enhancements in liquid metal functionality. [ 84,86,87 ] For example, Guo et al. [ 88 ] found that in situ reduced gold‐coated liquid metal nanodroplets exhibited stronger photothermal conversion effects.…”
Section: Liquid Metal Compositesmentioning
confidence: 99%
“…[83][84][85] In many cases, such shells exhibit enhancements in liquid metal functionality. [84,86,87] For example, Guo et al [88] found that in situ reduced gold-coated liquid metal nanodroplets exhibited stronger photothermal conversion effects. Liquid gallium@reduced graphene oxide core-shell nanoparticles synthesized by Zhang et al [89] demonstrated improved photothermal and photoacoustic properties.…”
Section: Liquid Metal Core-shell Compositesmentioning
confidence: 99%